Pengembangan Media Pembelajaran Augmented Reality untuk Materi Sistem Pencernaan Manusia - Karentius, Maret Rista; Hardiyantari, Oktavia (Jambura Journal of Informatics, 2025)
The rapid development of information technology, particularly in mobile devices, has opened new opportunities for educational innovation. This study aims to develop Augmented Reality (AR)-based learning media for eighth-grade junior high school students on the topic of the human digestive system. The research employed a Research and Development (RD) methodology using the Multimedia Development Life Cycle (MDLC) model, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. The resulting application features interactive elements, including quizzes and 3D Augmented Reality visualizations of digestive organs to enhance students' understanding of complex concepts. Feasibility testing involved assessments by media experts, material experts, and students, achieving feasibility percentages of 75%, 91%, and 89%, respectively, classifying the media as "very feasible." Effectiveness testing, based on the gain score from pre-test and post-test results, yielded an N-Gain value of 0.80, categorized as "high." These findings indicate that the developed learning media are both feasible and effective for use in supporting the teaching and learning process, particularly in enhancing student engagement and comprehension of the human digestive system.Perkembangan teknologi informasi yang pesat, khususnya pada perangkat mobile, telah membuka peluang baru dalam inovasi pendidikan. Penelitian ini bertujuan mengembangkan media pembelajaran berbasis Augmented Reality untuk siswa kelas VIII SMP pada materi sistem pencernaan manusia. Penelitian ini menggunakan metode Research and Development (RD) dengan model Multimedia Development Life Cycle (MDLC) yang meliputi tahap konsep, desain, pengumpulan bahan, pembuatan, pengujian, dan distribusi. Produk yang dihasilkan adalah aplikasi pembelajaran interaktif yang dilengkapi dengan kuis serta visualisasi 3D organ pencernaan manusia berbasis Augmented Reality untuk meningkatkan pemahaman konsep yang kompleks. Uji kelayakan dilakukan melalui penilaian ahli media, ahli materi, dan siswa, dengan hasil persentase kelayakan berturut-turut sebesar 75%, 91%, dan 89%, sehingga masuk dalam kategori "sangat layak." Uji efektivitas berdasarkan nilai N-Gain dari hasil pre-test dan post-test memperoleh nilai 0,80 yang termasuk dalam kategori "tinggi." Hasil tersebut menunjukkan bahwa media pembelajaran yang dikembangkan layak dan efektif digunakan untuk mendukung proses pembelajaran, khususnya dalam meningkatkan keterlibatan dan pemahaman siswa terhadap materi sistem pencernaan manusia.